Synthesis of Functionalized Azobiphenyls and Azoterphenyls with Improved Solubilities for Switching Applications - Köhl, Isabel; Lüning, Ulrich (Synthesis, 2014)
Nine new azo compounds, in particular azobiphenyls and azoterphenyls, have been synthesized and their photochemical switching has been investigated. 4,4′-Dihalogenated azobenzenes were generated by oxidative copper-mediated coupling of respective anilines followed by Suzuki–Miyaura cross-coupling reaction. The elongated azobenzenes carry functional groups at the terminal 4-positions and additional methyl substituents at the central benzene rings. While the introduction of two methyl groups improved the solubility of the resulting azo compounds considerably, the introduction of four methyl groups was less successful with respect to solubility. Differences were also found in the photochemical behavior for the dimethyl and the tetramethyl derivatives.
Keywords: azo compounds; cross-coupling; isomerization; photochemistry; switching